Smoking Behavior With Gingiva Health Status In Adolescent Boys Ages 15-19 Years In Wangunsari Hamlet Setiawaras Village Cibalong Sub-District Tasikmalaya District - nuary, tessha (Poltekkes Kemenkes Yogyakarta, 2020)
The prevalence of smokers in children and adolescents in Indonesia has increased by 19.4%. Smoking can cause pathological conditions in the oral cavity, one of which is gingivitis. Objective: To determine the relationship of smoking behavior factors based on the number of cigarettes and duration of smoking with gingival health status in adolescent boys aged 15-19 years in Wangunsari Hamlet, Setiawaras Village, Cibalong Sub-District, Tasikmalaya District. Method: observational analytic with the cross-sectional approach. A sample of 48 adolescents boys aged 15-19 years. Data analysis uses frequency distribution and Spearman correlation. Results: 35 respondents (72.92%) had moderate categories of smoking behavior based on the number of cigarettes, 35 respondents (72.92%) had heavy categories of smoking behavior based on smoking duration, 28 respondents (58.33%) had moderate gingival health status. Spearman correlation test results for the relationship of smoking behavior factors based on the number of cigarettes with gingival health status obtained p-value of 0.003 (<0.05), while for those based on smoking duration with gingival health status obtained p-value of 0,000 (<0.05) ) shows that smoking behavior factors based on a number of cigarettes and duration of smoking have a positive and meaningful relationship with gingival health status. Conclusion: there is a relationship between smoking behavior factors based on the number of cigarettes and duration of smoking with gingival health status in adolescent boys aged 15-19 years in Wangunsari Hamlet, Setiawaras Village, Cibalong Sub-District, Tasikmalaya District.